Ethical and responsible tourism managing sustainability in local tourism destinations - Koščak, Marko; O'Rourke, Tony (London New York Routledge, Taylor & Francis Group, Earthscan, 2023)
"Ethical and Responsible Tourism explains the methods and practices used to manage the environmental impact of tourism on local communities and destinations. This new edition takes into account recent global events such as the Covid-19 health crisis, the impacts of the war in Ukraine on tourism in neighbouring regions, and the consequences of the energy and cost of living crisis. The three core themes of the book - destination management, environmental and social aspects of ethical sustainable development, and business impacts - are discussed across both topic and case study chapters, alongside explanatory editorial analysis with all chapters clearly signposted and interlinked. The case studies address specific and practical examples from a global range of examples including sites in Australasia, Central America, Europe, Asia, North America and South America. In this new edition, further case studies are included from the USA and Japan, as well as new examples from Brazil, Croatia and Malta. Used as a core textbook, the linking of theory in the topic chapters, and practice gained through case studies, alongside further reading and editorial commentary, Ethical and Responsible Tourism provides a detailed and comprehensive learning experience. Specific case studies can be used as standalone examples as part of a case teaching approach, and the editorial and discussion elements are designed to be suitable for those simply seeking a concise overview, such as tourism professionals or potential investors in sustainable tourism projects. This revised edition continues to be essential reading for students, researchers and practitioners of tourism, environmental and sustainability studies"--
Includes bibliographical references and index.
Keywords: Sustainable tourism; Sustainable tourism -- Case studies; Tourism -- Environmental aspects; Tourism -- Moral and ethical aspects; Tourism -- Environmental aspects -- Case studies; Tourism -- Moral and ethical aspects -- Case studies